PEMBERDAYAAN TP-PKK MELALUI PELATIHAN PENGOLAHAN LIMBAH ORGANIK RUMAH TANGGA MENJADI PUPUK KOMPOS DI DESA SETAIL GENTENG BANYUWANGI - Octaviani, Nayla; Citra, Amelia Ariadna Mahawa; Winanti, Ananda Ines Putri; Prastowo, Sigit (PAPUMA: Journal of Community Services, 2025)
Each village in Indonesia has distinct potential, encompassing natural resources, culture, and economic activities. Setail Village, located in Genteng District, Banyuwangi Regency, is one of the villages with significant agricultural potential. However, its large population has increased the volume of household waste, particularly organic waste. Organic waste is often disposed of directly in landfills (TPA), despite its potential to be recycled into compost. Processing organic waste into compost not only reduces waste but also supports environmentally friendly agriculture, adhering to the 3R principles (reduce, reuse, recycle). The composting process can be simple and inexpensive, utilizing used containers and additional materials such as soil or animal manure. Through this practice, the Setail Village community has the opportunity to reduce waste while supporting local food security.